2015
DOI: 10.1590/s1413-70542015000500001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Classification of Floodplain Soils in the Porto Alegre Metropolitan Region, Rs, Brazil

Abstract: In the Porto Alegre metropolitan region (PAMR) there are a significant proportion of floodplain soils, mainly Planosols and Gleysols, in relation to upland soils. This study aimed to evaluate the morphological, chemical and physical characteristics, and to classify floodplain soils in the PAMR. Six soil profiles were evaluated under different sedimentary lithologies and drainage classes, and samples were collected for chemical and physical analyzes. Two orders of mineral soils (Planosols and Gleysols) and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…This is an advantage for plant development, provided that there are no other limiting factors. There are reports of the occurrence of dystrophic Planosols in Brazil (Silva Neto et al, 2015;Oliveira Júnior et al, 2019), but eutrophic Planosols like those found in this study have been described in the semiarid region (Ferreira et al, 2016).…”
Section: Resultssupporting
confidence: 46%
“…This is an advantage for plant development, provided that there are no other limiting factors. There are reports of the occurrence of dystrophic Planosols in Brazil (Silva Neto et al, 2015;Oliveira Júnior et al, 2019), but eutrophic Planosols like those found in this study have been described in the semiarid region (Ferreira et al, 2016).…”
Section: Resultssupporting
confidence: 46%
“…The average accuracy of the IPDS areas was 72.7 %, and was 100, 75, and 50 % for the Plintaquults, Albaquults, and Aquents, respectively (Table 4). These accuracies were satisfactory, considering the greater difficulty in mapping these areas in comparison to better drained areas because of the significant heterogeneity of soils inherent to hydromorphic environments (Coringa et al, 2012;Guimarães et al, 2013;Silva Neto, 2015). Moreover, the terrain variations are small in these areas, which makes it more difficult to differentiate soil classes using terrain variables.…”
Section: Resultsmentioning
confidence: 99%